Seasoned equity offerings and corporate financial management - BARCLAY, Michael J. (Institutional Knowledge at Singapore Management University, 2021)
We assume executives managing corporate financial policy consider the firm's current and target leverage, investment plans, anticipated cash flows, and consequences of alternative sequences of financing transactions, operating within efficient markets. Our analysis yields time-series and cross-sectional predictions for management of investment spending and leverage; use of maturity, priority, and convertibility covenants; and management of dividends, share repurchases, cash balances, and credit lines. Our evidence from 8608 SEOs covering 1970–2015 is consistent with implications of our theory, helps to resolve an array of issues in corporate finance, and offers a step toward a more unified analysis of rational corporate financial management.